A FELZÁRKÓZÁS MÉRÉSÉNEK KÉRDÉSEI ÉS ASPEKTUSAI A VISEGRÁDI ORSZÁGOK ESETÉBEN - Tóth, Zsuzsanna (Közép-Európai Közlemények, 2019)
In 2004 the European Union accomplished an expansion of unprecedented scale in the scope of which ten new member states joined the 15 existing members of the community in one huge step. During the period leading up to and immediately following the expansion, a great number of analyses and reports saw the light of day that attempted to evaluate the further development potentials of the ten new member countries. These analyses and reports, however, considered the European Union as if it were a uniform and homogenous population or set and used it as a basis for comparison in their projections. They did so even though this assumption already fails to hold true for the EU15 and that the subsequent accessions and the global economic crisis exacerbated, and in fact, accentuated the differences in the member states’ levels of development. Therefore, leaving these false assumptions behind, to gain a more reliable and workable evaluation of the convergence processes of the four Visegrad countries and to make an adequate comparison of the results, I find it highly advisable to consider the problem of catching-up from various aspects and to lay down different performance levels. My analysis only encompasses real convergence, which means that I only analyse the catching-up process and opportunities of the four Visegrad countries with a view to their GDP per capita figures, their main labour market indicators and productivity. In my paper, I present the results of the convergence calculations I did as well as the conclusions that may be drawn from them with the help of multi-level analyses that at the same time allow for describing both the functionality and the efficiency of the European Union.